The non-invasive evaluation technique of patellofemoral joint stress: a systematic literature review - Wang, Baofeng; Mao, Zheng; Guo, Jiaming; Yang, Jin; Zhang, Shengnian (Frontiers in Bioengineering and Biotechnology, 2023)
Patellofemoral joint stress (PFJS) is an important parameter for understanding the mechanism of patellofemoral joint pain, preventing patellofemoral joint injury, and evaluating the therapeutic efficacy of PFP rehabilitation programs. The purpose of this systematic review was to identify and categorize the non-invasive technique to evaluate the PFJS. Literature searches were conducted from January 2000 to October 2022 in electronic databases, namely, PubMed, Web of Science, and EBSCO (Medline, SPORTDiscus). This review includes studies that evaluated the patellofemoral joint reaction force (PJRF) or PFJS, with participants including both healthy individuals and those with patellofemoral joint pain, as well as cadavers with no organic changes. The study design includes cross-sectional studies, case-control studies, and randomized controlled trials. The JBI quality appraisal criteria tool was used to assess the risk of bias in the included studies. In total, 5016 articles were identified in the database research and the citation network, and 69 studies were included in the review. Researchers are still working to improve the accuracy of evaluation for PFJS by using a personalized model and optimizing quadriceps muscle strength calculations. In theory, the evaluation method of combining advanced computational and biplane fluoroscopy techniques has high accuracy in evaluating PFJS. The method should be further developed to establish the "gold standard" for PFJS evaluation. In practical applications, selecting appropriate methods and approaches based on theoretical considerations and ecological validity is essential.